Manganese-based mullite catalyst rich in A-site metal defects as well as preparation method and application of manganese-based mullite catalyst

By constructing A-position metal defects on the surface of mullite-type oxides, a manganese-based mullite catalyst rich in A-position metal defects was prepared, which solved the problem of the existing catalyst being easily toxicized under a humid atmosphere, and achieved the Efficient Cl-VOCs degradation and improved stability.

CN119386856APending Publication Date: 2025-02-07HUAZHONG NORMAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411601633.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing manganese oxide catalysts are susceptible to toxicity by water and chlorine under a humid atmosphere, resulting in reduced catalytic activity and toxic by-product generation, and are unable to efficiently degrade chlorinated volatile organic compounds (Cl-VOCs).

Method used

By constructing A-position metal defects on the surface of mullite-type oxides, the activation ability of oxygen and water molecules is enhanced, thereby preparing a manganese-based mullite catalyst rich in A-position metal defects. The catalyst constructs metal defects through the urea-driven NH4+ sacrificial substitution method, which improves the catalyst's anti-chlorine/water poisoning properties and catalytic activity.

Benefits of technology

The catalyst showed efficient chlorobenzene conversion and stability in a humid environment, with a chlorobenzene conversion of 90%, and did not show a significant decrease after 1440 minutes of stability test, which significantly improved the degradation ability of Cl-VOCs and anti-toxic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386856A_ABST
    Figure CN119386856A_ABST
Patent Text Reader

Abstract

The invention provides a manganese-based mullite catalyst rich in A-site metal defects as well as a preparation method and application of the manganese-based mullite catalyst. The preparation method of the catalyst comprises the following steps: mixing and dissolving rare earth metal salt and manganese salt under a stirring condition, adding organic acid and urea, heating until gel is formed, drying and calcining to obtain the manganese-based mullite catalyst rich in A-site metal defects. According to the invention, a urea-driven NH4 < + > sacrificial substitution method is utilized to selectively etch surface rare earth metal atoms, so that the catalyst with the surface rich in metal defects is formed. The construction of the A-site metal vacancy causes the B-site metal to be more electron-deficient. The limited A vacancy is used as a molecular oxygen activation site, and the oxidized B site is used as a water molecule activation site. The activation of water molecules promotes the hydrolysis dechlorination process, so that Cl in chlorobenzene is accelerated to be separated from the surface of the catalyst in the form of HCl, active site poisoning is avoided, generation of toxic and side products is inhibited, and the catalytic combustion activity and stability of chlorobenzene are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a manganese-based mullite catalyst rich in A-site metal defects and a preparation method and application thereof. Background Art

[0002] Chlorinated volatile organic compounds (Cl-VOCs) are widely present in industries such as machinery manufacturing, petrochemicals, pharmaceuticals, and spraying. They are released into the atmosphere through volatilization, leakage, and emissions, which can lead to problems such as ozone layer depletion and photochemical smog. The high electronegativity of the chlorine element in Cl-VOCs makes it difficult to degrade in nature, and it is easy to accumulate in organisms, showing strong environmental persistence. Although catalytic combustion technology has been widely used in Cl-VOCs treatment due to its advantages such as low energy consumption and high efficiency, the technology still faces key problems such as the generation of toxic by-products due to excessively high operating temperatures, catalyst chlorine poisoning, and water poisoning. Based on this, traditional catalysts that rely on a single active oxygen species to remove Cl-VOCs can no longer meet actual needs, and there is an urgent need to develop a more efficient and stable catalytic system.

[0003] Manganese is one of the elements widely distributed in the earth's crust. Its oxides (MnO2, Mn2O3, Mn3O4, etc.) have the advantages of low cost and easy availability of raw materials in preparation, and can effectively catalyze the combustion of volatile organic compounds (VOCs). However, this type of manganese oxide has certain limitations, such as high ignition temperature, easy deactivation, poor thermal stability and easy sintering. At the same time, the existing manganese oxide catalysts are easily poisoned by water and chlorine in a humid atmosphere, and the conversion temperature of Cl-VOCs is too high due to the inability to efficiently activate molecular oxygen.

[0004] In contrast, mullite-type oxides (AB2O5) exhibit many advantages due to their unique twin field crystal structure. This structure endows mullite-type oxides with excellent stability, strong oxygen storage / release capacity, abundant oxygen species, and controllable structural defects. These characteristics enable mullite-type oxides to exhibit higher activity and stronger stability in the catalytic combustion reaction of chlorinated volatile organic compounds (Cl-VOCs), showing great application potential. Therefore, it is urgent to develop a new mullite-based (SMO) catalyst to improve the degradation ability of Cl-VOCs and the resistance to chlorine / water poisoning under humid conditions. Summary of the invention

[0005] In view of this, the present invention proposes a manganese-based mullite catalyst rich in A-site metal defects and its preparation method and application. The catalyst enhances the activation ability of the SMO material to oxygen and water molecules by constructing metal defects on the SMO surface, thereby having good catalytic activity and resistance to chlorine / water poisoning.

[0006] In a first aspect, the present invention provides a method for preparing a manganese-based mullite catalyst containing an A-site metal defect, comprising the following steps:

[0007] Under stirring conditions, rare earth metal salt and manganese salt are mixed and dissolved, and then organic acid and urea are added, heated to form a gel, dried and calcined to obtain a manganese-based mullite catalyst rich in A-site metal defects.

[0008] In the present invention, for metal oxides such as mullite, in order to maintain the main skeleton structure, the radius of the A-site metal (rare earth metal) is relatively larger than that of the B-site metal (manganese), so the A-site metal generally uses a lanthanide element.

[0009] On the basis of the above technical solution, preferably, the rare earth metal salt is a lanthanide metal salt, and the lanthanide metal salt is selected from Y(NO3)·6H2O and / or Sm(NO3)3·6H2O;

[0010] The manganese salt is selected from one or more of Mn(CH3COO)2·4H2O, Mn(CH3COO)2·2H2O, Mn(NO3)2 or Mn(CH3COO)2.

[0011] More preferably, the rare earth metal salt of the present invention is Y(NO3)·6H2O and / or Sm(NO3)3·6H2O. These two substances have good water solubility and are easily dissolved in aqueous solution, which is convenient for preparing solutions and carrying out subsequent chemical reactions or treatment processes. Compared with other forms of rare earth metal salts, these two rare earth metal nitrates are relatively stable in air and aqueous solution, are not prone to chemical changes, and are conducive to storage and transportation. As rare earth elements, yttrium and samarium have rich electronic energy level structures and can participate in a variety of chemical reactions. They can serve as active centers or additives of catalysts to enhance the catalytic effect. In addition, yttrium nitrate and samarium nitrate, as raw materials, can be prepared into the desired final product by simple chemical methods, thereby simplifying the production process.

[0012] More preferably, the manganese salt of the present invention is Mn(CH3COO)2·4H2O or Mn(CH3COO)2·2H2O. These two substances also have good solubility in water and are easy to be prepared into a uniform solution, which is convenient for subsequent chemical reactions or process treatments. Compared with other forms of manganese salts, acetic acid manganese salts are more stable in the air, less prone to chemical changes, and are conducive to long-term storage and transportation. As a catalyst precursor, acetic acid manganese salts can provide highly active manganese ions, participate in a variety of chemical reactions, and can significantly enhance the catalytic effect in redox reactions. In addition, acetic acid manganese salts are less toxic and have less impact on the environment than other manganese salts, which is more in line with the green chemistry principles pursued by modern industry.

[0013] More preferably, in the present invention, the molar ratio of the rare earth metal salt to the manganese salt is 1:2.

[0014] On the basis of the above technical solution, preferably, the organic acid is citric acid. In the present invention, the citric acid is further selected from citric acid monohydrate and / or anhydrous citric acid.

[0015] In the present invention, in order to ensure uniform dispersion of metal ions, preferably, the mass ratio of the citric acid to the metal ions in the rare earth metal salt is 1 to 1.5:1.

[0016] On the basis of the above technical solution, preferably, the molar ratio of the urea to the sum of the metal ions in the rare earth metal salt and the metal ions in the manganese salt is 1 to 4:1.

[0017] By adopting the above technical solution, the molar ratio of urea to the sum of metal ions in rare earth metal salts and metal ions in manganese salts is controlled to be 1 to 4:1, and the present invention can effectively adjust the metal defect concentration in the SMO material. This appropriate metal defect concentration can not only ensure that the material has high activity, but also avoid the problem of insufficient or excessive defects caused by too many or too few metal ions. Therefore, the material prepared by this technical solution is not only highly active, but also has good stability, and can show excellent performance in practical applications, such as efficiency improvement in catalytic reactions.

[0018] On the basis of the above technical solution, preferably, the heating temperature is 100° C. to form a gel.

[0019] By adopting the above technical solution, the present invention can achieve a rapid and uniform gelation process. This temperature is conducive to promoting the cross-linking reaction between molecules in the precursor solution and accelerating the evaporation of water, thereby effectively forming a dense and uniform gel structure. In addition, this temperature condition can also reduce the occurrence of side reactions and avoid material decomposition or other structural damage caused by excessively high temperature.

[0020] On the basis of the above technical solution, preferably, the drying temperature is 100° C. and the drying time is 24 hours.

[0021] On the basis of the above technical scheme, preferably, the calcination includes two calcination processes, the first calcination temperature is 300-500°C, and the time is 6-8h; the second calcination temperature is 500-800°C, and the time is 6-8h; the first calcination and the second calcination are carried out continuously and uninterruptedly.

[0022] In a second aspect, the present invention relates to a manganese-based mullite catalyst rich in A-site metal defects (SMO-X, wherein X represents the molar ratio of urea to metal cations) prepared by the above method.

[0023] On the basis of the above technical solution, preferably, the molar content of the A-site metal defect accounts for 5% to 15% of the total molar content of the catalyst.

[0024] By adopting the above technical solution, the surface properties of the catalyst can be effectively adjusted so that it has a higher active site density. The metal defect content within this range will neither be too low to provide sufficient active sites nor too high to cause the catalyst structure to be unstable or the activity to decrease. Therefore, within this preferred range, the catalyst can not only show high catalytic efficiency and good selectivity, but also maintain a long service life, and is suitable for a variety of industrial catalytic reaction processes, thereby improving the overall economic benefits.

[0025] More preferably, the molar content of the A-site metal defect accounts for 10% of the total molar content of the catalyst.

[0026] On the basis of the above technical solution, preferably, the manganese-based mullite is SmMn2O5 and / or YMn2O5.

[0027] On the basis of the above technical solutions, preferably, it involves the use of the above-mentioned manganese-based mullite catalyst rich in A-site metal defects in catalyzing the combustion of chlorobenzene.

[0028] In a third aspect, the present invention provides a method for catalyzing the combustion of chlorobenzene in a wet environment, comprising:

[0029] Under the action of the above-mentioned SMO-X catalyst rich in A-site metal defects, chlorobenzene is catalyzed to burn in a humid environment.

[0030] By adopting the above technical scheme, the present invention uses a catalyst rich in A-site metal defects for the degradation of chlorobenzene in a humid environment, the A-site metal defects can promote oxygen activation to reduce the conversion temperature of pollutants, and the B-site oxidized Mn sites can promote the activation of water molecules, which is helpful for the removal of chlorine from chlorobenzene. The synergistic activation of oxygen and water molecules can further enhance the activity and stability of the manganese-based mullite catalyst in the combustion process of chlorobenzene.

[0031] On the basis of the above technical solution, preferably, the temperature of the chlorobenzene catalytic combustion is 100 to 400 degrees Celsius and the relative humidity is 0 to 100%.

[0032] More preferably, in the present invention, the temperature of the catalytic combustion of chlorobenzene does not exceed 200° C., and the relative humidity is not higher than 80%.

[0033] The manganese-based mullite catalyst rich in A-site metal defects and its preparation method and application provided by the present invention have the following beneficial effects compared with the prior art:

[0034] (1) The present invention uses urea-driven NH4 + The sacrificial substitution method selectively constructs the A-site metal defect on the surface of the binary metal oxide to prepare the SMO-X catalyst resistant to water poisoning. The catalyst exhibits high catalytic activity in a wide temperature range. In a humid atmosphere with a relative humidity of 80%, at 200°C, the SMO catalyst is severely poisoned by water vapor. In contrast, under the action of the SMO-X catalyst of the present invention, the chlorobenzene conversion rate reaches 90%, and after 1440 minutes of stability testing, the chlorobenzene conversion rate does not show a significant decrease. The catalyst still has excellent resistance to chlorine / water poisoning, and the reaction rate can reach 14 times that of the SMO catalyst.

[0035] (2) The purification effect of the SMO-X catalyst provided by the present invention is better than that of traditional transition metal catalysts, and its preparation process is simple, easy to operate, low cost, high conversion rate of chlorine-containing volatile organic matter, strong operating stability, and has obvious industrial application value.

[0036] (3) The SMO-X catalyst of the present invention is used for the catalytic combustion reaction of chlorine-containing volatile organic compounds. It can be in the form of particles or loaded as a coating on a honeycomb carrier such as cordierite to prepare a monolithic porous catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 This is a comparison chart of the catalytic combustion activity of chlorobenzene in dry and wet atmospheres of Examples 1 to 3 of the present invention;

[0039] Figure 2 This is a comparison chart of the catalytic combustion activity of chlorobenzene in dry and wet atmospheres of Comparative Example 1 of the present invention;

[0040] Figure 3 This is a comparison chart of the catalytic combustion stability test of chlorobenzene under wet conditions at 200° C. for Example 2 of the present invention and Comparative Example 1;

[0041] Figure 4 This is a comparison chart of the catalytic combustion activity of chlorobenzene of the SMO-2 catalyst prepared in Example 2 and Examples 4 to 7 of the present invention under different relative humidity conditions. DETAILED DESCRIPTION

[0042] In a humid environment, when using unmodified manganese oxide catalysts to degrade chlorobenzene, the active sites on the catalyst surface are easily poisoned by both water and chlorine, and the lattice oxygen is difficult to activate, resulting in an excessively high catalytic conversion temperature, which in turn triggers the formation of toxic by-products.

[0043] In view of the fact that the prior art is not as good as the inventor's expectations, the inventor made the present invention through further exploration and research.

[0044] The inventors found in practice that by constructing metal defects, confined sites for oxygen activation can be constructed on the surface of mullite oxides, and surface electron transfer can be regulated to enhance the catalyst's ability to activate oxygen and water molecules.

[0045] In view of this, the present invention is a simple urea-driven NH4 + The sacrificial substitution method constructs an appropriate amount of A-site metal defects on the mullite surface. The catalyst can achieve dual activation of oxygen and water molecules. On the one hand, the A-site metal defect provides a confined activation site in the pore for oxygen; at the same time, the vacancy causes the adjacent Mn site to exhibit electron-deficient characteristics, thereby enhancing the adsorption and activation ability of water molecules. The activation of water molecules promotes the accelerated detachment of chlorine atoms (Cl) in chlorobenzene from the catalyst surface in the form of HCl, avoids poisoning of active sites, and inhibits the generation of toxic byproducts. This synergistic activation strategy of oxygen and water molecules greatly improves the catalytic combustion activity and stability of chlorobenzene, and demonstrates excellent Cl-VOC degradation ability.

[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The following are specific examples of the present invention. The sources of the materials mainly involved in the examples are as follows, and the remaining materials not shown are conventional commercially available products.

[0048] Samarium nitrate hexahydrate (CAS No.: 7439-89-6), tetramethylammonium hydroxide (CAS No.: 75-59-2), and polyether PF127 (CAS No.: 9003-11-6) used in the present invention are all purchased from Shanghai Aladdin Co., Ltd.; manganese acetate tetrahydrate (CAS No.: 6156-78-1), urea (CAS No.: 57-13-6), citric acid monohydrate (CAS No.: 5949-29-1), and octanol (CAS No.: 111-87-5) are all purchased from Sinopharm Group.

[0049] Example 1

[0050] This embodiment provides a method for preparing a manganese-based mullite catalyst rich in A-site metal defects, which specifically comprises the following steps:

[0051] (1) Dissolve 0.008 mol of Sm(NO3)3·6H2O and 0.016 mol of Mn(CH3COO)2·4H2O in 100 mL of deionized water and stir for 1 h.

[0052] (2) adding 0.05 mol of citric acid monohydrate and 0.024 mol of urea to the solution prepared in step (1), heating to 90° C., and continuing to stir until a gel is formed;

[0053] (3) The gel obtained in step (2) was placed in an oven at 110° C. and dried overnight to obtain a precursor, and the precursor was then kept at 300° C. for 1 h and at 800° C. for 5 h to obtain the SMO-1 catalyst.

[0054] The molar content of the metal defect at the A position of the SMO-1 catalyst obtained in this example accounts for 5.4% of the total molar content of the catalyst.

[0055] Example 2

[0056] The method for preparing a manganese-based mullite catalyst rich in A-site metal defects in this embodiment is different from that in Embodiment 1 in that: in step (2), the amount of urea used is 0.048 mol.

[0057] The molar content of the metal defect at the A position of the SMO-2 catalyst obtained in this example accounts for 10.1% of the total molar content of the catalyst.

[0058] Example 3

[0059] The method for preparing a manganese-based mullite catalyst rich in A-site metal defects in this embodiment is different from that in Embodiment 1 in that: in step (2), the amount of urea used is 0.096 mol.

[0060] The molar content of the metal defect at the A position of the SMO-4 catalyst obtained in this example accounts for 7.8% of the total molar content of the catalyst.

[0061] Comparative Example 1

[0062] This comparative example provides a method for preparing a pure phase SMO (denoted as SMO-0) without A-site metal defects, which specifically comprises the following steps:

[0063] (1) Dissolve 0.01 mol of Sm(NO3)3·6H2O and 0.02 mol of Mn(CH3COO)2·4H2O in 100 mL of deionized water, add 0.04 g of polyether PF127 surfactant, and stir for 10 min.

[0064] (2) Add a 25% tetramethylammonium hydroxide solution to the solution in step (1) until the pH value of the solution is 9, then add 2 mL of H2O2 (30 wt.%) and 2 mL of octanol, and then add a 25% tetramethylammonium hydroxide solution to adjust the pH value to 11, then stir and age at room temperature for 2 h, and place the filtered precipitate in an oven at 105° C. and dry overnight to obtain a precursor.

[0065] (3) The precursor of step (2) was kept at 500° C. and 800° C. for 8 h respectively to obtain a SMO catalyst, which was recorded as SMO-0.

[0066] Performance Testing

[0067] (1) The catalytic activity of the manganese-based mullite catalysts rich in A-site metal defects prepared in Examples 1 to 3 and the SMO catalyst prepared in Comparative Example 1 was tested (reference for the test method: https: / / doi.org / 10.1021 / acscatal.3c01871). Specifically, the following steps were performed:

[0068] The test experiment was carried out in a fixed bed reactor, with a catalyst loading of 0.3 g and a particle size of 20-40 mesh; the initial gas concentrations under the drying conditions were: chlorobenzene was 100 ppm, oxygen was 10 vol%, nitrogen was the carrier gas, and the mass space velocity was 20000 mL . g -1. h -1 , the test temperature is 100~400℃; the relative humidity under humid conditions is 0~100%. The test results are as follows Figure 1 , 2 shown.

[0069] Depend on Figure 1 It can be seen that compared with the dry condition, the activity of the SMO-X catalysts prepared in Examples 1 to 3 under the humid atmosphere is improved to varying degrees, and T90 is reduced from 306°C, 216°C, and 263°C to 286°C, 196°C, and 239°C, respectively, indicating that the A vacancy can enhance the water activation ability of the catalyst, thereby resisting the poisoning of the active sites by water vapor.

[0070] Depend on Figure 2 It can be seen that the catalytic activity of the SMO catalyst prepared in the comparative example for chlorobenzene under a humid atmosphere is that SMO-0 is poisoned by water vapor and its activity decreases compared with that under dry conditions.

[0071] (2) The stability test was performed on the SMO-2 catalyst prepared in Example 2 and the SMO-0 catalyst prepared in Comparative Example 1 (reference for the test method: https: / / doi.org / 10.1021 / acscatal.3c01871). The test results are as follows: Figure 3 shown.

[0072] Depend on Figure 3 It can be seen that: in a humid atmosphere, the SMO-2 catalyst prepared in Example 2 and the SMO-0 catalyst prepared in Comparative Example 1 will be quickly poisoned and deactivated, and the conversion rate will drop from 90% to about 50%; while SMO-2 shows extremely high stability. After running at 196°C for 1440 minutes, the chlorobenzene conversion rate did not show a significant decrease, indicating that its resistance to chlorine / water poisoning is significantly enhanced.

[0073] Taking Example 2 as an example, the catalytic activity of the SMO-X catalyst under different humidity conditions is explored, and the following Examples 4 to 7 are given. The humidity conditions of Examples 4 to 7 are shown in Table 1 below. The test method refers to the performance test (1), and the test results are shown in the attached Figure 4 shown.

[0074] Table 1 Relative humidity data table of Example 2, Example 4 to 7

[0075] Example 2 Example 4 Example 5 Example 6 Example 7 Relative humidity / % 80 0 40 60 100

[0076] Depend on Figure 4 It can be seen that the catalyst exhibits the best activity at a relative humidity of 80%, and the catalytic activity is the best, and 90% conversion of chlorobenzene can be achieved at 200°C. This shows that the construction strategy of A-site metal defects is an effective strategy to achieve chlorobenzene removal in a high humidity environment.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a manganese-based mullite catalyst rich in A-site metal defects, characterized in that: The preparation method comprises the following steps: Under stirring conditions, rare earth metal salt and manganese salt are mixed and dissolved, and then organic acid and urea are added, heated to form a gel, dried and calcined to obtain a manganese-based mullite catalyst rich in A-site metal defects.

2. The preparation method according to claim 1, characterized in that The rare earth metal salt is a lanthanide metal salt, and the lanthanide metal salt is selected from Y(NO3)·6H2O and / or Sm(NO3)3·6H2O; The manganese salt is selected from one or more of Mn(CH3COO)2·4H2O, Mn(CH3COO)2·2H2O, Mn(NO3)2 or Mn(CH3COO)2.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the rare earth metal salt to the manganese salt is 1:

2.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the organic acid to the metal ions in the rare earth metal salt is 1 to 1.5:

1.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the urea to the sum of the metal ions in the rare earth metal salt and the metal ions in the manganese salt is 1 to 4:

1.

6. A manganese-based mullite catalyst rich in A-site metal defects, characterized in that: The catalyst is prepared by the preparation method according to any one of claims 1 to 5.

7. The manganese-based mullite catalyst rich in A-site metal defects as claimed in claim 6, characterized in that The molar content of the A-site metal defect accounts for 5% to 15% of the total molar content of the catalyst.

8. The manganese-based mullite catalyst rich in A-site metal defects as claimed in claim 7, characterized in that The manganese-based mullite is SmMn2O5 and / or YMn2O5.

9. Use of the manganese-based mullite catalyst rich in A-site metal defects as claimed in any one of claims 6 to 8 in catalyzing the combustion of chlorobenzene.

10. A method for catalyzing the combustion of chlorobenzene in a wet environment, characterized in that: The method comprises: catalyzing the combustion of chlorobenzene under the action of the manganese-based mullite catalyst rich in A-site metal defects as claimed in any one of claims 6 to 8.